2002
DOI: 10.1086/340349
|View full text |Cite
|
Sign up to set email alerts
|

Four Years of Monitoring Blazar PKS 2155−304 withBeppoSAX: Probing the Dynamics of the Jet

Abstract: PKS 2155-304 is one of the brightest blazars in the X-ray band. It was repeatedly monitored with BeppoSAX during three long campaigns of about 2 days each in November of 1996November of , 1997November of and 1999. The source underwent different states of intensity and was clearly variable with successive flares detected. This paper presents temporal and spectral analysis to study the X-ray variability trends for a blazar. The variability shows larger amplitude and shorter timescale at higher energies. The p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
116
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(127 citation statements)
references
References 55 publications
10
116
0
1
Order By: Relevance
“…Similar behaviour was also detected in other sources, such as PKS 2155-304 Zhang et al 2002a) or BL Lacertae (Böttcher et al 2003).…”
Section: Time Resolved Spectral Analysissupporting
confidence: 80%
See 3 more Smart Citations
“…Similar behaviour was also detected in other sources, such as PKS 2155-304 Zhang et al 2002a) or BL Lacertae (Böttcher et al 2003).…”
Section: Time Resolved Spectral Analysissupporting
confidence: 80%
“…Following the treatment of Zhang et al (2002a), we can express the cooling timescale t cool and the acceleration timescale t acc in the observer frame as a function of the photon energy E (in keV) as:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then it has been the target of a number of X-ray monitoring programmes. These studies indicated a red-noise type of variability at X-ray frequencies with the characteristic variability timescale of the order of days, and only little power corresponding to intraday flux changes (Zhang et al 1999(Zhang et al , 2002Tanihata et al 2001;Kataoka et al 2001). Frequent X-ray flares are typically characterized by symmetric profiles, superimposed short (∼10 ks) smaller-amplitude flickering, and a variety of soft and hard lags changing from epoch to epoch.…”
Section: Introductionmentioning
confidence: 99%